Effects of increasing levels of lasalocid supplementation on growth performance, serum biochemistry, ruminal fermentation profile, in vitro nutrient digestibility, and gas production of growing goats - Basmaeil, Saeid M.; Suliman, Gamaleldin M.; Al Garadi, Maged A.; Al-Badwi, Mohammed A.; Abdelrahman, Mutassim M.; Al-Harbi, Fahad S.; El-Waziry, Ahmed M.; Alhidary, Ibrahim A.; Swelum, Ayman A. (Frontiers in Veterinary Science, 2023)
Introduction Lasalocid is a feed additive widely used in ruminant nutrition and plays a crucial role in improving livestock productivity, digestibility, immunity, and overall wellbeing. The current study was conducted to investigate the effect of different levels of lasalocid (LAS) supplementation on growth performance, serum biochemistry, ruminal fermentation profile, in vitro nutrient digestibility, and gas production of growing goats. Methods A total of 60 growing Aardi male goats with an average body weight of 17.12 kg (3-month-old) were used for an 84-day trial. Animals were randomly divided into four treatment groups with 5 replicates of 3 goats each. All four groups were provided with a basal diet supplemented with lasalocid (LAS) at 0 (without supplementation; LAS0), 10 (LAS10), 20 (LAS20), or 30 (LAS30) ppm LAS/kg dry matter (DM). Feed intake was measured weekly, and goats were weighed every 2 weeks for an evaluation of the performance parameters. Blood samples were collected for the measurement of biochemical variables. In vitro nutrient digestibility and gas production were evaluated. Results and discussion The supplementation of LAS at level 30 ppm/kg DM increased (P < 0.05) the body weight gain and average daily gain without linear or quadratic effect. The serum concentrations of high-density lipoprotein were significantly (P < 0.05) higher in the LAS20 group than in other groups with linear and quadratic effects, while low-density lipoprotein concentration was significantly lower in the LAS20 group than in LAS0 and LAS30 with a linear effect. Different levels of lasalocid supplementation had no effect on the ruminal fermentation profile, in vitro gas production, and nutrient digestibility. In conclusion, the addition of LAS (20–30 ppm/kg DM) to the goat's diet can improve the growth performance and lipoprotein profile.